2009
DOI: 10.3109/17453670902947390
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional mechanical evaluation of joint contact pressure in 12 periacetabular osteotomy patients with 10-year follow-up

Abstract: Background and purpose Because of the varying structure of dysplastic hips, the optimal realignment of the joint during periacetabular osteotomy (PAO) may differ between patients. Three-dimensional (3D) mechanical and radiological analysis possibly accounts better for patient-specific morphology, and may improve and automate optimal joint realignment.Patients and methods We evaluated the 10-year outcomes of 12 patients following PAO. We compared 3D mechanical analysis results to both radiological and clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
77
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(89 citation statements)
references
References 28 publications
11
77
0
1
Order By: Relevance
“…However, the number of patients with an acetabular or femoral head cyst before PAO was low and we encourage caution with any interpretations. Since six patients had a decrease in cyst volume, a regenerative process can take place in the bony tissue after PAO where the biomechanical loading on the hip changes [2,11]. In our study, this was supported by all bone cysts except two being located anterolaterally in the hip, where degeneration in the dysplastic hip often is found [7] and where peak contact stress is localized [21,27].…”
Section: Discussionsupporting
confidence: 65%
“…However, the number of patients with an acetabular or femoral head cyst before PAO was low and we encourage caution with any interpretations. Since six patients had a decrease in cyst volume, a regenerative process can take place in the bony tissue after PAO where the biomechanical loading on the hip changes [2,11]. In our study, this was supported by all bone cysts except two being located anterolaterally in the hip, where degeneration in the dysplastic hip often is found [7] and where peak contact stress is localized [21,27].…”
Section: Discussionsupporting
confidence: 65%
“…Finite element analysis has shown that reconstructive procedures such as the Bernese periacetabular osteotomy (PAO) can increase joint contact area and decrease joint contact pressures [6,36] but cannot reach predicted normal values, probably because of the irregular shape of dysplastic hips [20,74]. Medium-term results (5.5 years to 15 years) after PAO show a rate of conversion to THA between 7% and 15% [19,36,43,68].…”
Section: Discussionmentioning
confidence: 99%
“…Acetabular deficiency and malalignment result in an abnormal force transfer across the hip joint leading to pathologically elevated cartilage stresses [1,2]. Pathological cartilage stresses accumulate over time affecting cartilage metabolism [3].…”
mentioning
confidence: 99%
“…The mechanical goal of acetabular reorientation is to decrease articular surface contact stresses by increasing the contact area in affected hips [1,2,6]. Several investigators have created biomechanical models of dysplastic hips.…”
mentioning
confidence: 99%
See 1 more Smart Citation